A single centre experience of local perforator flaps in oncoplastic breast surgery; a cross-sectional study. (December 2022) - Zeeshan, Sana; Vohra, Lubna Mushtaque; Shamsi, Uzma Shoaib; Zahid, Nida; Ali, Danish; Khan, Nargis; Garusi, Cristina
Abstract: Background & objectives: Various oncoplastic techniques have emerged over the years to preserve breast cosmesis and symmetry without compromising the principles of tumor excision. One of the newer techniques for breast volume replacement to achieve symmetry and cosmesis is the use of fasciocutaneous pedicled chest wall perforator flaps or local perforator flaps (LPF). The objectives of this study were to document the details of the surgical procedure as well as patient-reported satisfaction and well-being following the procedure using a validated BREAST-Q tool among Pakistani women. Materials & methods: This cross-sectional study was conducted from March 2019 to February 2021 enrolling 25 female patients who underwent breast conservative surgery using LPF for breast tumors at The Aga Khan University Hospital, Karachi. Data related to the procedure was collected on a pre-designed proforma. Cosmetic outcomes and patient satisfaction were evaluated using 2 scales from BREAST-Q BCT domain version 2.0. The questionnaire was self-administered by the patients during their routine follow-up in the clinic. Data was analyzed using the Statistical Package for Social Sciences (SPSS) version 23. Mean (SD)/median (IQR) were computed for quantitative variables and frequency and percentages were calculated for qualitative variables. 2 sample t -test was applied. P-value ≤0.05 was considered significant. Results: 25 patients underwent LPF with a mean age of 47 ± 13.1 years. 8 LICAP, 7 AICAP, and 10 LTAP flaps were performed. Two postoperative complications of wound site erythema were encountered. 23 women were eligible for the BREAST-Q survey. Median (IQR) postoperative satisfaction with breasts and physical well-being chest (equivalent Rasch transformed score) was 100 (41) and 76 [18] respectively. We found high satisfaction with breasts and comparable physical well-being among Pakistani women after LPF surgeries. Conclusion: Local perforator flaps in oncoplastic breast-conserving surgery are a good option showing high satisfaction with breasts and physical well-being in Pakistani women. Highlights: Local perforator flaps are a good technique for breast volume replacement. BREAST-Q is a validated tool used to assess patient satisfaction after surgery. Patients were satisfied with local perforator flap in partial breast reconstruction. Local perforator flaps have minimal peri-operative morbidities. Patient selection with healthy perforators is vital for safe and good outcomes.